An analysis of government revenue and expenditure in relation to national accounts - Broderick, J. D. (Statistical and Social Inquiry Society of Ireland, 1960)
The influence of government action on the course of the economy is nowadays very wide and often decisive. For this reason it is desirable that methods, other than those of the traditional government accounting, be used to analyse the effect of government action on the rest of the economy and to provide data additional to those available in the traditional accounts, as a basis for the crucial decisions which have to be made. No single set of accounts is adequate for this purpose. The national accounts of the country provide an integrated framework which embraces the whole economy and it, therefore, appears to be a worth-while task to organise and present in detail the accounts for recent years of the Government sector within such a framework.
Read before the Society, 8 April 1960
Keywords: Government expenditure in Ireland; Government revenue in Ireland; Irish national income accounts; 314.15